Aplicación de fertilizantes orgánicas de liberación controlada y activadores fisiológicos en plántulas de previvero de palma africana (Elaeis guinnensis), en la zona de Babahoyo - Andrade Torres, Jonathan José (2014)
The African palm is one of the products of more importance in the, at the moment you cultivate approximately 210000 have; with an average of productivity of 5.9 t of pure oil for hectare, value considered under compared with other countries that you/they obtain 6 to 7 t/ha. The biggest cultivate area is carried out in the counties of Emeralds, Sacred Domingo, The Ríos and Guayas with around 92 % of the total production of the country. The objective of this investigation was to determine the agronomic behavior of plants of pre-vivero palm, to the application of organic fertilizers of controlled liberation, in the area of Babahoyo. The investigation was made in the Ability of Agricultural Sciences, located in the km 7,5 of the road Babahoyo-Montalvo. The variety of palm oil bottle Tenera was investigated, with 8 treatments with the help of Humicrop and Humitop like sources of alone applied organic fertilizers and in combinations to the 30-60 and 90 days of the transplant, in parcels of 10 cases. They were distributed at random in a design of complete blocks. For the evaluation of stockings the test was used from Tukey to 95 % of probability. During the cycle it was evaluated: plant height, diameter of shafts, number of leaves for plant, root longitude and area to foliate........